Fulfilling the Rights to Accessibility of Persons with Disabilities in Pemalang State Court Legal Services - Enggal Aflah Syafiqoti; Tet Hediati (Faculty of Sharia, State Islamic University KH. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2022)
Human rights are rights that exist in every human being. These rights are obtained by every human being or can be called equal to one another. Persons with Disabilities have the same Human Rights as society in general. One of them is the Rights of Persons with Disabilities in the Pemalang District Court because the Pemalang District Court is a community service which is certainly the center of attention for every community. So the purpose of this study is to find out the implementation of the fulfillment of Accessibility Rights for Persons with Disabilities in the District Court based on existing regulations and Constitutional Rights. So that this research is expected to make public awareness more open to persons with disabilities and for the government to pay more attention. This study uses empirical juridical research methods with a qualitative approach that uses interactive analysis techniques to analyze the problems that exist in this study. The data used are primary data obtained from interviews and direct observation at the research location, as well as secondary data obtained from written reports and documents obtained from the literature. The results of this study indicate that the implementation of the fulfillment of Accessibility Rights for Persons with Disabilities at the Pemalang District Court is not in accordance with Constitutional Rights and regulations that have been made by the government. At the Pemalang District Court there are still some that have not been fulfilled in terms of physical and non-physical accessibility. And in reality, there are still many in our own society who view people with one-sided disabilities who cannot work and cannot do other positive things like society in general. So that many of their lives are deprived because they are hampered in terms of mobility. In the Regional Government itself, there are also those who have not made specific regulations regarding the rights of Persons with Disabilities. Which regulations must be made in each region to support the survival of Persons with Disabilities.